Methods of determining the content of pollutants in the combustion products of plasma water and organic compositions of the reactor portable gas analyzer "Quintox" KM9106; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Tyudelekov E. A. (Nuclear technologies as integral part of engineering science in the modern world, 2014)
Заглавие с экрана